You are on page 1of 13

# MATH 108-07S1

Q1. [20 marks]

## (a) [8 marks] The augmented matrix for the system is

 
1 2 −1 1
1 3 2 k
3 6 −3 k
The row operations
R2 := R2 − R1 , R3 := R3 − 3R1
lead to  
1 2 −1 1
0 1 3 k − 1
0 0 0 k−3
So for the system to be consistent, we need k = 3.

## When k = 3 the matrix is  

1 2 −1 1
0 1 3 2
0 0 0 0
Solve by back substitution with z = t to obtain

y + 3t = 2, i.e. y = 2 − 3t
x + 2(2 − 3t) − t = 1, i.e. x = −3 + 7t

## Geometrically, the system describes three planes which intersect in a line.

(b) [4 marks]
(i)
A A A2 A A
(I − A)(I + )=I −A+ − = I −A+ + = I
2 2 2 2 2
and similarly
A
(I +
)(I − A) = I
2
A
So I − A is invertible and (I − A)−1 = I + .
2
(ii) If A is invertible,

## A−1 (A2 ) = −A−1 A

i.e. (A−1 A)A = −I
I A = −I
A = −I

1
(c) [4 marks]
(i) If x is in the natural domain of f , we must have x − 1 ≥ 0 and so the natural
domain is [1, ∞).

## (ii) Clearly x − 1 is an increasing function so that f is also increasing and therefore

1 − 1.
(Alternately, show that f ′ (x) > 0.)

To find f −1 , start with the equation x = y − 1 giving

y = f −1 (x) = x2 + 1.

(d) [4 marks] Consider the inequality on each of the two cases x < 4 and x ≥ 4.

## If x ≥ 4, |x − 4| = x − 4 so that x − 4 > 3, i.e. x > 7.

S
The solution is therefore (−∞, 1) (7, ∞).

2
Q2. [17 marks]
(a) [6 marks]
(i)
lim− f (x) = lim− (1 − x2 ) = 1 and
x→0 x→0
lim f (x) = lim+ cos x = 1
x→0+ x→0
2
Since also, f (0) = 1 − 0 = 1, f is continuous at x = 0.
(ii)
f (h) − f (0) cos h − 1
lim+ = lim+ =0
h→0 h h→0 h
f (h) − f (0) (1 − h)2 − 1
lim− = lim− =0
h→0 h h→0 h
So f is differentiable at x = 0 and f ′ (0) = 0.

## (b) [5 marks] By implicit differentiation,

 
dy dy
2x + 2y + 2a x + y = 0
dx dx
dy
∴ (y + ax) + x + ay = 0
dx
dy x + ay
and so =−
dx y + ax
In the case a = −1,
dy x−y
=− =1
dx y−x
so that the curve is the straight line y = x.
(This also follows from the original equation which becomes x2 + y 2 − 2xy = 0,
i.e. (x − y)2 = 0, or y = x.)
(c) [6 marks]
0
(i) This is an indeterminate form of the type so we can use L’Hôpital’s rule
0
and obtain
1
ln x x
lim = lim
x→1 x2 − x x→1 2x − 1
1 1
= lim = = 1.
x→1 2x − x
2 2−1

0
(ii) This is also of the form . Applying L’Hôpital’s rule gives
0
cos ax − cos bx −a sin ax + b sin bx
lim = lim
x→0 x2 x→0 2x
0
which is still of the form . Applying L’Hôpital’s rule again gives
0
cos ax − cos bx −a2 cos ax + b2 cos bx b2 − a2
lim = lim = .
x→0 x2 x→0 2 2

3
Q3. [17 marks]

## (a) [10 marks]

x−2
y=
x2
(i) When y = 0, x = 2 so that the intercept with the x axis is the point (2, 0).

(ii) Since x = 0 is not in the domain of f (and lim f (x) = −∞), there is a vertical
x→±0
asymptote at x = 0 (the y axis).

x→±∞

## (iii) f ′ (x) > 0 when either

(i) 4 − x > 0 and x3 > 0, or when
(ii) 4 − x < 0 and x3 < 0.
I.e. when either (i) 0 < x < 4 or (ii) x > 4 and x < 0 — (which case is
impossible.)

## So f is increasing on the interval (0, 4).

S
It follows that f is decreasing on (−∞, 0) (4, ∞).
1
When x = 4, y = f (x) = so that (using the first derivative test), f has a local
8
1
maximum at the point (4, ).
8

(iv) f is concave up when f ′′ (x) > 0, i.e. when x > 6, i.e. on the interval (6, ∞).
f is concave downSwhen f ′′ (x) < 0, i.e. when x < 6 and x 6= 0. So f is concave
down on (−∞, 0) (0, 6).
Since concavity changes when x = 6, there is an inflexion point when x = 6, i.e.
1
at the point (6, ).
9

4
(v)
y
1
(4, )
8
· 1
(6, )
9
·

·
(2, 0) x

5
(b) [7 marks]

y = 3 − x2

y
Area A

x √
3

## (i) A(x) (the area of the rectangle) is

A(x) = 2xy = 2x(3 − x2 ) = 6x − 2x3 .

Note that the natural domain of A is [0, 3]. This is defined by the problem!

(ii) So we need to maximize A on [0, 3].

dA
= 6 − 6x2 = 0 when x = 1
dx
(The case x = −1 is not in the domain of A.)

Finally √
A(0) = 0, A( 3) = 0, A(1) = 6 − 2 = 4
So the maximum area is 4.

6
Q4. [17 marks]

(a) [6 marks]
(i)
Z   Z Z Z
− 21 −2x − 12
2x − sin 3x + e dx = 2 x dx − sin 3x dx + e−2x dx
1
2x 2 cos 3x e−2x
= 1 + − +C
2
3 2
1 1 1
= 4x 2 + cos 3x − e−2x + C
3 2
√ 1 du 1 dx
(ii) Let u = x = x 2 so that = √ , i.e. √ = 2 du.
dx 2 x x
Then

sin x
Z Z
√ dx = 2 sin u du
x
= −2 cos u + C

= −2 cos x + C.

(b) [6 marks]

y = 3x + 2

A1
3

A2
2

(i)
1
1 3 7
Z
(3x + 2) dx = A1 + A2 = ×1×3+1×2= +2 = .
0 2 2 2

7
f (x) = 3x + 2

k−1 k 1
n n

(ii)

n
X 1 k
Consider Rn = f( )
k=1
n n
n  
X 1 3k
= +2
k=1
n n
n n
3 X 2X
= k + 1
n2 k=1 n k=1
3 n(n + 1) 2
= + n
n2 2  n
3 1
= 1+ +2
2 n
3 7
Therefore lim Rn = + 2 = as above.
n→∞ 2 2

8
(c) [5 marks]
Z ∞
2
In = x2n e−x dx
Z0 ∞
dv −x2 x2n+1
= u dx where u = e and v =
0 dx 2n + 1
Z ∞
du
= uv |∞
0 − v dx
0 dx
2
∞ Z ∞ 2n+1
x2n+1 e−x x 2
= − · −2xe−x dx
2n + 1 0 2n + 1
0
Z ∞
2 2
= 0−0+ x2n+2 e−x dx
2n + 1 0
2
= In+1
2n + 1

2n + 1
Therefore In+1 = In .
2

9
Q5. [14 marks]
(a) [3 marks] Write this equation as

dy
y = cos x.
dx
Integrating both sides of the equation with respect to x gives:
Z Z
dy
y dx = cos x dx
dx
Now use the chain rule to get
Z Z
y dy = cos x dx

Integrating the LHS with respect to y and the RHS with respect to x gives

y2
= sin x + C
2
Since the required integral curve goes through the point ( π2 , 1),

1 π 
= sin + C = 1 + C
2 2
So C = − 21 and the equation of the integral curve is

y2 1
= sin x −
2 2

R
2dx
(b) [5 marks] The integrating factor is ρ = e = e2x .
Multiplying the DE by this gives:
 
dy
+ 2 y e2x = 5 e3x e2x
dx
d
y . e2x = 5 e5x

dx
y . e2x = e5x + C
y = e3x + C e−2x

10
(c) [6 marks]
(i) Since there is originally 50 grams of sugar present, the DE becomes
dS
= k (50 − S)
dt
Separating the variables, and using the chain rule gives
1 dS
= k
(50 − S) dt
1
Z Z
dS
dt = k dt
(50 − S) dt
1
Z Z
dS = k dt
(50 − S)
1
Z Z
dS = − k dt
(S − 50)
ln(S − 50) = −kt + C

## (Students may need to make a substitution to find the LH integral.)

Taking exponentials gives

S − 50 = e−kt+C = A e−kt

where A = eC .
The general solution to the differential equation is

S = 50 − A e−kt .

Since at t = 0, S = 0,

0 = 50 − A e0 = 50 − A

so A = 50 and hence

S = 50 − 50 e−kt = 50 (1 − e−kt )

as required.

S −→ 50

## That is, all 50 grams of sugar gets converted.

11
Q6. [15 marks]
(a) [6 marks]
(i) The first and second order partial derivatives are:

fx = 2x − 6y fy = 3y 2 − 6x
fxx = 2 fyy = 6y fxy = − 6 ( = fyx )

3y 2 − 18y = 0
3y(y − 6) = 0

## So y = 0 and x = 0 or y = 6 and x = 18.

The critical points are (0, 0) and (18, 6).

## (iii) Use the “D” test.

2
point fxx fyy fxy D = fxx fyy − fxy
(0, 0) 2 0 −6 −36
(18, 6) 2 36 −6 36

## A saddle occurs at (0, 0) since D < 0 and fxx > 0.

A minimum occurs at (18, 6) since D > 0 and fxx > 0.

## (b) [4 marks] Differentiating W wrt t twice holding x constant gives

∂W
= (−c) cos(x − ct)
∂t
and
∂2W
= (−c)2 (− sin(x − ct)) = − c2 sin(x − ct)
∂t2
Differentiating W wrt x twice holding t constant gives
∂W
= cos(x − ct)
∂x
and
∂2W
= − sin(x − ct)
∂x2
So
2∂2W 2 ∂2W
c = − c sin(x − ct) =
∂x2 ∂t2
and the wave equation is satisfied by W (x, t).

12
(c) [5 marks]
(i) The contour of f (x, y) which passes through the point (0, 0) is given by setting

(x − y) (x2 + y 2 ) = 0

## so that the contour line is the line y = x.

This line breaks the region close to the critical point into two regions.
(See diagram below.)
(ii) By testing points in these regions we can work out where f is positive and where
f is negative. If a maximum occurs at (0, 0), then f < 0 in all regions. If a
minimum occurs at (0, 0), then f < 0 in all regions . Any other case means that
a saddle has to occur at the critical point.

−3 − − y=x

point sign of f − 2 − +

(−1, 0) − − − + +
1
(1, 0) +

−3 −2 −1 1 2 3
− −1 + +

− + −2 + +
+
+ +−3 +

13